Resource use and biophysical constraints of Scottish agriculture - Viglia, Silvio; Franzese, Pier Paolo; Zucaro, Amalia; Blackstock, Kirsty L.; Matthews, Keith B.; Ulgiati, Sergio (Ecological Questions, 2013)
Agriculture is a fundamental sector of economy and society that ensures food supply, classified by the Millennium Ecosystem Assessment among the so-called “provisioning ecosystem services”. Due to the increase of food demand worldwide, farmers are shifting more and more towards intensive agriculture. This trend is connected to the unsustainable consumption of natural resources, most often exceeding the carrying capacity of natural ecosystems. In this paper, the resource use and biophysical constraints of Scottish agriculture were investigated at regional and national levels by means of the Emergy Synthesis method. The study focused on two main agroecosystems: 1) the Cairngorms National Park (CNP) and 2) the national agricultural sector of Scotland as a whole. The evolution of the agricultural sector was explored over time (years 1991, 2001, 2007), accounting for local renewable and non-renewable resources as well as imported resources. Performance and sustainability indicators were then calculated with and without including human labor and economic services (money flows). In the year 2007, the Emergy Yield Ratio (EYR) of the Scottish agricultural sector was about 46% of the same indicator calculated for the CNP (2.65 versus 5.72, respectively). A higher Environmental Loading Ratio (ELR) was calculated for the national sector than for CNP (1.25 versus 1.02, respectively). The Emergy Sustainability Index (ESI) was 2.12 for the national sector and 5.60 for CNP. Such figures were calculated without including the emergy flows supporting labor and services. If the latter are also accounted for, the ESI of the national level and CNP drop by a factor 5.6 and 3.9, respectively. Such variations suggest that larger flows of non-renewable resources strongly affect the environmental performance, increasing the dependence on non-renewable resources supporting the larger economic system in which the agricultural sectors are embedded in.